Validation of Serious Games for Health Education - Ferreira, Suiane Costa (2024)
The aim of this study is to present the validation of serious games as educational technologies in healthcare. This is a methodological study with a quantitative approach. Three board games were developed: Imunizagame; Guerreiros de Saludis: Ataque ao Stress; and ISTAR: Uma batalha pela saúde. Once development was complete, the validation stage began. The evaluators were members of the research group belonging to different backgrounds. MEEGA+ (Model for the Evaluation of Educational Games) was used to evaluate the games. The results address the overall quality of the game, its usability, player experience and possible areas for improvement. The three games were rated as excellent, with emphasis on the attractive design, promotion of interactivity between players, appropriate levels of challenge and the generation of knowledge in their respective areas of expertise.